Pembuatan Biopori dan Sumur Resapan untuk Mengatasi Kekurangan Air Tanah di Perumahan Villa Mutiara, Tangerang Selatan - Ratna Safitri; Rahma Purisari; Muhammad Mashudi (Institut Pertanian Bogor, 2019)
Villa Mutiara Housing is located in Ciputat Sub District, South Tangerang. This housing does not yet have clean water supply facilities, both government and private water treatment plants. This is what causes the majority of the population in Villa Mutiara Housing to use ground water for their daily needs. Mass extraction of ground water automatic water pumps has impacted on depletion of groundwater reserves, especially during the dry season. The environmental conditions of Villa Mutiara housing are also minimal green open space due to the number of pavements, this results in flooding during the rainy season because rainwater cannot be absorbed by the soil as well as the limited capacity of city channels. The Science and Technology Program for the community aims to empower the middle class community to save the surrounding environment, especially to restore ground water reserves and anticipate floods. The method used is focus group discussion (FGD), making bio pores and infiltration wells by involving citizens, and socializing the results of activities through social media. Villa Mutiara housing was chosen as a pilot location for bio pores production and infiltration wells, because the residents of the housing complex were mostly middle class with a good level of education. The results of this activity were the installation of 11 bio pores holes and 1 infiltration well as a pilot to be developed and carried out by residents independently.